The book of unconformities : speculations on lost time - Raffles, Hugh, 1958- (Pantheon Books, 2020)
"Drawing on history, anthropology, accounts of exploration, and observation, Hugh Raffles undertakes a journey to places north--to investigate the uncertain survival and unsettling presence of ancient stones and the alluring glimpse that these stones open into lives and meanings now faded from view. He travels to Iceland, to the once standing Odin Stone in the Orkney Islands, to the Isle of Lewis in the Hebrides, to the coal mines of Spitsbergen, and to the Museum of Natural History in New York to see the Cape York meteorite that Admiral Peary brought back from Greenland. Raffles also journeys to his own everyday north, on a crowded uptown New York City subway, rattling beneath Broadway, hurtling to a place called Marble Hill--the subterranean marble that soared into peaks, weathered into wooded hills, extruded and folded to form an island that once roamed upon an ancient ocean. Raffles's meditation leads him to understand how these fundamental objects and places can seem to lose their solidity and become inextricable from historic account and the architecture of human fate"--